Flight training and alterations in cortical characteristics - Chen, Xi; Chu, Qi; Wang, Hongming; Tan, Xi; Duan, Mingjun; Luo, Cheng (Frontiers in Human Neuroscience, 2025)
BackgroundPiloting is a highly specialized profession. The purpose of this study was to investigate the effects of longitudinal flight training on the cortical characteristics of the brain.MethodsMagnetic resonance imaging of 25 flight cadets and 24 controls was performed twice over a 2-year period. The gray matter thickness, cortical surface area and sulcal depth of the two groups were compared. The relationships between altered cortical characteristics and flight training days were investigated through correlation analysis.ResultsThe results indicated that flight training was associated with certain parameters of brain structure. Specifically, in the left rostral anterior cingulate area, the flight group displayed prominent gyri, whereas the control group exhibited sulci. The structural changes in these two groups followed completely opposite trends.ConclusionIn conclusion, the affected areas are primarily concentrated in brain regions associated with multisensory integration and multitasking, which may reflect neural adaptations induced by flight training.